Effect of anthraquinone on NSSC pupling of P.deltoides - Maryam Rostaei (Regional Information Center for Science and Technology (RICeST), 2011)
This research was performed to improve the properties of the pulp made of Aspen Deltoides, using antraquinone(AQ) catalizer. Neutral sulfite semichemical (NSSC) method in three efficiency levels of 55, 60, and 65% was applied. Cooking situations was selected as: Specific Temperature (175˚ C) , Time (Variable) , Specific Percentage of Chemicals 14% and Anthraquinone 0.1% . In all stages of cooking, weight ratio of sodium sulfide to sodium bicarbonate was set as 4.5/1. The ratio of cooking liquid to chips was 5/1. The results indicated that AQ causes an increase in efficiency and a significant decrease in Kappa. Researches also indicated that by the use of AQ, strength indexes of the paper such as strength of burst, tearing, tensile, Ring Crush Test and Corrugating Medium Test increases. Optical experiments on hand sheets following addition of AQ, indicated increase in brightness and decrease in opacity.